Dante Through the Eyes of his Contemporaries: a Collection of the Fourteenth-century Minor Tuscan Political and Civil Poetry on Dante - Pancini, Marialaura (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
This paper analyses a selection of political and civil 14th-century minor Tuscan lyrical texts, where authors use Dante’s biography and literature to compose political and civil verses. Through biographical and informatics research I selected a corpus of texts regarding the selected topic and genre. The purpose was to find similarities and differences between different texts, authors, and contexts. What emerges is a heterogeneous landscape that demonstrates some recurring themes in different texts.